Precipitation over Northern South America and Its Seasonal Variability as Simulated by the CMIP5 Models (2015)
RESUMEN: Northern South America is identified as one of the most vulnerable regions to be affected by climate change. Furthermore, recent extreme wet seasons over the region have induced socioeconomic impacts of wide proportions. Hence, the evaluation of rainfall simulations at seasonal and interannual time scales by the CMIP5 models is urgently required.Here,we evaluated the ability of seven CMIP5models (selected based on literature review) to represent the seasonalmean precipitation and its interannual variability over northern SouthAmerica.Our results suggest that it is easier formodels to reproduce rainfall distribution during boreal summer and fall over both oceans and land. This is probably due to the fact that during these seasons, incoming radiation and ocean-atmosphere feedbacks over Atlantic and Pacific oceans locate the ITCZ on the Northern Hemisphere, as suggested by previous studies.Models exhibit the worse simulations during boreal winter and spring, when these processes have opposite effects locating the ITCZ. Our results suggest that the models with a better representation of the oceanic ITCZ and the local low-level jets over northern South America, such as the Choco low-level jet, are able to realistically simulate the main features of seasonal precipitation pattern over northern South America.